Here, we are required to identify the dependent and independent variables, the dependency relationship in the situation.
- The independent and dependent variables are the weight of the dog and the amount of food it should respectively.
- The dependency relationship is thus; The amount of food a dog should eat is a function of the weight of the dog
- The dependency relationship using the function notation is; f(x) = {function of x}.
- The independent variable in this situation is the weight of the dog while the amount of food the dog should eat is the dependent variable. The above is evident from the statement; <em>T</em><em>he amount of food a dog should eat depends on the weight of the </em><em>dog</em><em>.</em>
- <em>According</em><em> </em><em>to </em><em>the </em><em>premise</em><em> </em><em>given </em><em>in </em><em>the </em>question, it is evident that the dependency relationship is;. The amount of food a dog should eat is a function of the weight of the dog
- The dependency relationship can be written mathematically using the function notation as;. f(x) = {function of x}.
Read more:
brainly.com/question/11239214
Answer:
1 pie and 75% of another pie
Step-by-step explanation:
Answer:
![\frac{2}{4} inch](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B4%7D%20inch)
Step-by-step explanation:
Step 1
List the length of the wingspan of the five butterflies
![\frac{1}{4}, \frac{1}{4}, 1, \frac{2}{4}, \frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D%2C%20%5Cfrac%7B1%7D%7B4%7D%2C%201%2C%20%5Cfrac%7B2%7D%7B4%7D%2C%20%5Cfrac%7B3%7D%7B4%7D%20%20)
Step 2:
The two butterflies with the shortest wingspan has a wing length of
inches each.
Step 3:
Total length of the wingspan of the two butterflies with the shortest wingspan
= ![=\frac{1}{4} +\frac{1}{4} \\ = \frac{2}{4}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%7D%7B4%7D%20%2B%5Cfrac%7B1%7D%7B4%7D%20%5C%5C%0A%20%20%20%20%20%20%20%3D%20%5Cfrac%7B2%7D%7B4%7D%20)
Final answer:
= ![\frac{2}{4} inch](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B4%7D%20inch)
Answer:
nuber 1
Simplifying
3x + 2y = 35
Solving
3x + 2y = 35
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2y' to each side of the equation.
3x + 2y + -2y = 35 + -2y
Combine like terms: 2y + -2y = 0
3x + 0 = 35 + -2y
3x = 35 + -2y
Divide each side by '3'.
x = 11.66666667 + -0.6666666667y
Simplifying
x = 11.66666667 + -0.6666666667y